The Responsibility of a Notary For Deeds Not Read In The Presence of The Parties Is Examined Based on Law Number 2 of 2014 Concerning The Position of a Notary - Ngatiran (Legalis : Journal of Law Review, 2024)
The notary, as a public official, has the responsibility to provide services to community members who require assistance in the drafting of written instruments, especially authentic deeds in the field of civil law. The existence of the notary is an implementation of the law of evidence. The Republic of Indonesia is a rule of law, based on the principle of the rule of law, ensuring certainty, order, and legal protection centered on truth and justice. Through the instruments drafted, the notary must provide legal certainty to the community utilizing notarial services. The purpose of this research is to understand how the notary assumes responsibility for the instruments they draft, which may cause issues due to the failure to read the instruments in the presence of the parties involved. This has been alleged as a violation of Law No. 30 of 2004, amended by Law No. 2 of 2014 concerning the notarial function carried out by a notary in the locality of Bencongan Kelapa Dua Tangerang, reported by NA (43) to the Criminal Investigation Unit (SPKT) of the South Tangerang Police Regional Office. The victim reported notaries AI, IG, and R, as well as other individuals involved, feeling deceived for about 3 years in the property title transfer process that remained incomplete from 2021 to 2023.